2009
DOI: 10.1007/s10483-009-1104-7
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of hot and cold fluids mixing in a T-junction for predicting thermal fluctuations

Abstract: Temperature fluctuations in a mixing T-junction have been simulated on the FLUENT platform using the large eddy simulation (LES) turbulent flow model and a sub-grid scale Smagorinsky-Lilly model. The normalized mean and root mean square temperatures for describing time-averaged temperature and temperature fluctuation intensity, and the velocity are obtained. The power spectrum densities of temperature fluctuations, which are key parameters for thermal fatigue analysis and lifetime evaluation, are analyzed. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Jayaraju et al [7] used LES to analyze the suitability of wall-functions in accurately predicting the thermal fluctuations acting on the duct walls due to turbulent mixing, and they found that LES has good agreement with the wall-resolved approach for the bulk velocity and temperature field. Zhu et al [8] discussed the effect of Richardson number and Reynolds number on the mixing process by LES turbulent flow model and a SGS Smagorinsky-Lilly model.…”
Section: Introductionmentioning
confidence: 99%
“…Jayaraju et al [7] used LES to analyze the suitability of wall-functions in accurately predicting the thermal fluctuations acting on the duct walls due to turbulent mixing, and they found that LES has good agreement with the wall-resolved approach for the bulk velocity and temperature field. Zhu et al [8] discussed the effect of Richardson number and Reynolds number on the mixing process by LES turbulent flow model and a SGS Smagorinsky-Lilly model.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature fluctuations in the mixing fluids may cause cyclical thermal stresses and subsequent thermal fatigue cracking of the pipe wall. Therefore, the thermal fatigue of tees is a very important technical issue affecting the safety of a piping system [1][2][3][4] . The European Union has funded an international project "Thermal Fatigue Evaluation of Piping System Tee-Connections".…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that LES is capable of predicting thermal fluctuations in turbulent mixing. Temperature fluctuations in a mixing tee were numerically predicted by Zhu et al [1] using LES with a sub-grid scale (SGS) Smagorinsky-Lilly (SL) model. Several cases were simulated in order to analyze the effects of varying Reynolds numbers and Richardson numbers on the mixing course and thermal fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…As the LES with accurate information on the ability to capture the turbulent fluctuation than the shear stress transport (SST), Reynolds stress equation model (RSM) turbulence model, with the improvement of computer performance, LES had rapid promotion and application in flow and heat transfer in recent years. Recent studies [1][2][3][4][5][6] have shown LES to be successful in predicting the mixing of hot and cold fluids in a T-junction. Simoneau et al [3] used LES for calculating turbulent flows in a T-junction in the nuclear field with different SGS models in the Star-CD platform, obtained the temperature and pressure fluctuations, shown that LES agreed well with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Their simulation results presented in normalized average temperature and normalized fluctuating temperatures are in good agreement with measurements. Zhu et al [6] used the LES with Smagorinsky-Lilly of SGS model to simulate the mixing processes in T-junctions. The numerical normalized mean and root mean square temperatures for describing time-averaged temperature and temperature fluctuation intensity agree with experimental data.…”
Section: Introductionmentioning
confidence: 99%